Central Giant Cell Granuloma in the Libyan Population- A 30 Year Retrospective Study - Hend M. Salama; Asma M. Ali Mussa; Ghada H. Haroun (Libyan Journal of Medical and Applied Sciences, 2025)
Central giant cell granuloma (CGCG) is a benign, uncommon intraosseous lesion typically found in the jawbones and characterized by having multinucleated giant cells in their histopathology. The etiology of this lesion is not clear, but it may be reactive, developmental, or neoplastic. It has a clinical and radiographic presentation that is similar to benign tumors. However, the World health organization (WHO) classifies it as a bone-related lesion rather than a true tumor. Although several studies have investigated both demographic and anatomical characteristics of CGCG in different populations, there is a lack of data regarding the Libyan population. It is essential to identify demographic and anatomical patterns to reach an accurate diagnosis and effective management. This retrospective cross-sectional study fills a significant gap in the literature by adding population-specific data. In this study we reviewed cases of CGCG diagnosed at the Faculty of Dentistry, Benghazi University, over a 30-year period from 1990 to 2021. Patient data—including age, gender, and lesion site—were collected and analyzed using descriptive statistics. Out of 2036 histopathological specimens, 33 cases (1.6%) were diagnosed as CGCG. The lesions showed female predominance (66.6%), with a mean age of 32.7 ± 18.6 years (range: 8–67 years). The mandible was more frequently affected (74.2%) than the maxilla, particularly in the posterior region. CGCG in the Libyan population exhibits a demographic and anatomical distribution consistent with findings in other populations, including a female predominance and a mandibular predilection. These results highlight the importance of population-specific data in guiding diagnosis and treatment.